Venom gland components of the ectoparasitoid wasp, Anisopteromalus calandrae - Perkin, Lindsey C (J Venom Res, 2015)
The wasp Anisopteromalus calandrae is a small ectoparasitoid that attacks stored product pest beetle larvae that develop inside grain kernels, and is thus a potential insect control tool. The components of A. calandrae venom have not been studied, but venom from other organisms contains proteins with potential applications, such as pest management tools and treatments for human diseases. We dissected female A. calandrae and collected venom and associated glands. Using high throughput sequencing, a venom gland transcriptome was assembled that contained 45,432 contigs, 25,726 of which had BLASTx hits. The majority of hits were to Nasonia vitripennis, an ectoparasitoid from the same taxonomic family, as well as other bees, wasps, and ants. Gene ontology grouped sequences into eleven molecular functions, among which binding and catalytic activity had the most representatives. In this study, we highlighted the most abundant sequences, including those that are likely the functional components of the venom. Specifically, we focused on genes encoding proteins potentially involved in host developmental arrest, disrupting the host immune system, host paralysis, and transcripts that support these functions. Our report is the first to characterize components of the A. calandrae venom gland that may be useful as control tools for insect pests and other applications.